Pathways of care in vascular surgery - Beard, Jonathan D.; Murray, Shelagh (Tfm Pub., 2002)
The book describes recent developments and best practice in vascular surgery, with an emphasis on multi-disciplinary care pathways. It is based upon a symposium held in Sheffield in June 2002 that aimed to improve the provision and equality of care for patients with peripheral arterial and venous disease.